Evaluation and Management of Kidney Calculi (Iranian Journal of Kidney Diseases, 2017)
Introduction. The recent change in the view towards nephrolithiasis from a benign isolated disease to a disorder associated with numerous systemic and chronic conditions has added to the importance of a more thorough and timely diagnostic and therapeutic intervention. Materials and Methods. Both original and review articles found via the PubMed search on recent evaluation and management strategies of urinary calculi were reviewed. These resources were integrated with the authors' knowledge of the field. Results. The emerging evidence attests to the association of nephrolithiasis with many morbid and fatal diseases, such as coronary heart disease, ischemic stroke, hypertension, chronic kidney insufficiency, malignancies, and bone loss, as well as the economic burden of urinary calculus on health system and work force. Conclusions. Findings of this review justify a timely and comprehensive workup and dietary-therapeutic measures in order to prevent, treat, and control the associated complications of this condition.